Stratifikasi Sosial dan Ketidaksetaraan Akses Keadilan: Analisis Sosio-Legal terhadap Sistem Peradilan Indonesia - Saifuddin, Muhammad Aris (HK-Publishing, 2025)
Abstract This study examines the impact of social stratification on inequality in access to justice within the Indonesian judicial system. Despite the constitutional guarantee of equality before the law, the realization of this principle remains inconsistent in practice. Employing a socio-legal approach, this research integrates normative-juridical and sociological-empirical analyses to explore how social structures influence the implementation of justice. Data were collected through an extensive literature review of legal journals, government policy documents, and socio-legal studies. The findings reveal that social stratification rooted in economic status, education, and political power significantly affects citizens’ ability to access justice. Structural barriers, such as litigation costs and limited legal aid; cultural barriers, including low legal literacy and negative perceptions of the judiciary; and institutional barriers, such as unequal quality of law enforcement and judicial infrastructure, collectively exacerbate inequality. The socio-legal analysis highlights a persistent gap between law in books and law in action, where formal legal norms often fail to deliver substantive justice due to social bias and power asymmetry. This study underscores the urgency of inclusive legal reform through enhanced public legal education, expanded legal aid, and institutional integrity strengthening. The findings contribute to the theoretical discourse on justice and provide empirical insights for developing responsive and socially grounded legal policies in Indonesia. Keywords: social stratification, access to justice, socio-legal approach, equality before the law. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh stratifikasi sosial terhadap ketidaksetaraan akses keadilan dalam sistem peradilan Indonesia. Fenomena kesenjangan hukum yang masih terjadi menunjukkan bahwa prinsip equality before the law belum sepenuhnya terwujud dalam praktik. Dengan menggunakan pendekatan sosio-legal, penelitian ini menggabungkan analisis normatif-yuridis dan sosiologis-empiris untuk memahami hubungan antara struktur sosial dan pelaksanaan hukum di lapangan. Data diperoleh melalui studi pustaka yang mencakup literatur hukum, dokumen kebijakan, dan penelitian empiris terkini. Hasil kajian menunjukkan bahwa stratifikasi sosial berbasis ekonomi, pendidikan, dan kekuasaan secara signifikan memengaruhi kemampuan masyarakat mengakses keadilan. Hambatan struktural (biaya perkara dan keterbatasan bantuan hukum), kultural (rendahnya literasi hukum dan persepsi negatif terhadap pengadilan), serta institusional (ketimpangan kualitas aparat dan infrastruktur) memperdalam kesenjangan hukum antara kelompok sosial. Analisis sosio-legal mengungkap adanya jurang antara law in books dan law in action, di mana hukum formal sering kali gagal mewujudkan keadilan substantif karena bias sosial dan dominasi kekuasaan. Penelitian ini menegaskan pentingnya reformasi hukum yang inklusif melalui peningkatan literasi hukum, perluasan bantuan hukum, dan penguatan integritas lembaga peradilan. Temuan ini berimplikasi pada pembaruan teori dan kebijakan hukum agar lebih responsif terhadap keadilan sosial serta membuka arah baru bagi penelitian sosio-legal di Indonesia. Kata kunci: stratifikasi sosial, akses keadilan, sosio-legal, kesetaraan hukum